THE GREEN ECONOMY IN UZBEKISTAN'S SUSTAINABLE DEVELOPMENT - Aхмадалиев Дилмурод Хурматиллоевич (European Science Publishing, 2025)
The shift towards a green economy is one of the main components of Uzbekistan's sustainable development agenda. This paper looks at both the quantitative and qualitative effects of the green economy between 2019 and 2024, particularly in relation to growth in renewable energy, reduction in carbon emissions, energy efficiency, and financial investment. The methods used for evaluation are mathematical and statistical. It has been found that capacity for renewable energy increased by 573 percent from 2019 to 2024 at an average annual growth rate of 15.5 percent. Carbon emissions were reduced by 4.2 percent, energy efficiency increased by 15.6 percent, and the share of GDP created by the green sector tripled during this period. The correlation coefficient shows a great opposite relationship between the growth of renewable energy and the reduction of emissions with a value of r = -0.84. These results can be utilized as proof that Uzbekistan's green transition is measurable and transformative; hence it should serve as an example for Central Asia looking to achieve sustainable development through similar means.
Keywords: Green economy, renewable energy, sustainable development, Uzbekistan, statistical modeling, economic efficiency.